2006
DOI: 10.1111/j.1467-9922.2006.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Novice Learners, Longitudinal Designs, and Event‐Related Potentials: A Means for Exploring the Neurocognition of Second Language Processing

Abstract: Research on the neurobiology of second language (L2) learning has historically focused on localization questions and relied on cross-sectional designs. Here, we describe an alternative paradigm involving longitudinal studies of adult, novice learners who are progressing through an introductory sequence of classroom-based L2 instruction. The goal of this paradigm is to determine how much L2 exposure is needed before learners incorporate L2 knowledge into their online comprehension processes, as reflected in sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
221
4
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(260 citation statements)
references
References 53 publications
32
221
4
3
Order By: Relevance
“…The present study, along with several other recent findings in the EEG literature (Osterhout et al 2006;Mueller et al 2005), offers evidence that the representational capacity of adult language users can change quickly during adult language learning. However, resource-based psycholinguistic models of processing complexity like those reviewed in the introduction have not yet addressed how the grammatical or representational resources used to parse complex sentences can change with language experience.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The present study, along with several other recent findings in the EEG literature (Osterhout et al 2006;Mueller et al 2005), offers evidence that the representational capacity of adult language users can change quickly during adult language learning. However, resource-based psycholinguistic models of processing complexity like those reviewed in the introduction have not yet addressed how the grammatical or representational resources used to parse complex sentences can change with language experience.…”
Section: Discussionmentioning
confidence: 83%
“…Recent work has shown that electrophysiology is sensitive to learning-related changes in adult language learners (Mueller et al 2005;Osterhout et al 2006). The hypothesis under investigation is that the ability to adapt to different forms of recursion remains plastic in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pattern of results across studies differed for the Different and Unique types: whereas neither of the two studies found a P600 in response to determiner number agreement violations, this was observed in the present study, albeit to a lesser degree than that found in response to demonstrative determiner number agreement (Similar type). Although it is possible that the discrepancy with the Osterhout et al (2006) study is due to the length of L2 instruction in the two groups of participants, this is unlikely because participants in that study had been learning the L2 for 8 months and participants in our study had a similar amount of instruction on average (though a broader range from only a few months to approximately 16 months). A different possibility is that participants in that study were not sensitive to determiner number agreement because this feature is not phonologically realized in…”
Section: Discussionmentioning
confidence: 47%
“…It is also interesting to note once again the dissociation between ERP and behavioral measures (although a d' measure may have been more informative than pure accuracy scores because L2 learners tend to have response biases): above-chance performance is not accompanied by implicit sensitivity as was also the case in the experiment. In a different study, Osterhout, McLaughlin, Pitkanen, Frenck-Mestre, and Molinaro (2006) found that native English speakers learning French showed a P600 in response to verbalperson agreement violations after four months of instruction but no sensitivity to noun phrase (NP) number agreement violations even after eight months of instruction. These results were interpreted in terms of cross-language similarity: although performed differently in the two languages, verbal-person agreement constitutes a feature of participants' L1 whereas NP number agreement does not and therefore takes longer to be incorporated into their online processing system.…”
Section: The Role Of Cross-language Similaritymentioning
confidence: 99%
“…Tu adores/*adorez le français.). Osterhout et al (2006) observed an interesting difference between native speakers and beginning L2 learners of French. Whereas native speakers of French displayed a P600 that reflects detection of a rule violation when confronted with an incorrect verb form, beginning L2 learners of French reacted with a N400 component.…”
mentioning
confidence: 95%